2016
DOI: 10.3892/ol.2016.4450
|View full text |Cite
|
Sign up to set email alerts
|

Nucleolar localization of Small G protein RhoA is associated with active RNA synthesis in human carcinoma HEp-2 cells

Abstract: Previous studies have demonstrated that the nuclear localization of ras homolog family member A (RhoA), with prominent concentration in the nucleolus, is a common feature in human cancer tissues and cancer cell lines. Although a previous study has demonstrated that the nuclear translocation of RhoA occurs via active transport, a process that occurs through importin α in a nuclear factor-κB-dependent manner, the mechanism, biological function and pathological meaning of the nucleolar residency of RhoA remain to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
2
2
0
Order By: Relevance
“…4G ). Fibrillarin showed exclusive nucleolar localization with a redistribution to small nucleoplasmic entities in the VPRBP knockdown cells, similar to previously described with actinomycin D treatment ( 39 ). To quantify nucleolar fragmentation, we measured the individual nucleolar area based on the fibrillarin staining as previously described ( 40 ), which showed that VPRBP knockdown cells have a much smaller nucleolar size compared (∼1.7 µm 2 ) with scrambled si-transfected cells (9.8 µm 2 ; Supplementary Fig S6A).…”
Section: Resultssupporting
confidence: 87%
“…4G ). Fibrillarin showed exclusive nucleolar localization with a redistribution to small nucleoplasmic entities in the VPRBP knockdown cells, similar to previously described with actinomycin D treatment ( 39 ). To quantify nucleolar fragmentation, we measured the individual nucleolar area based on the fibrillarin staining as previously described ( 40 ), which showed that VPRBP knockdown cells have a much smaller nucleolar size compared (∼1.7 µm 2 ) with scrambled si-transfected cells (9.8 µm 2 ; Supplementary Fig S6A).…”
Section: Resultssupporting
confidence: 87%
“…4G). Fibrillarin showed exclusive nucleolar localization with a redistribution to small nucleoplasmic entities in the VPRBP knockdown cells, similar to previously described with actinomycin D treatment 34 . A significant (~25%) reduction in fibrillarin and 40S ribosomal protein S8 (RPS8) expression, was observed with VPRBP siRNA2 (Fig.…”
Section: Vprbp Knockdown Induces Nucleolar Stress In Lncap Cellssupporting
confidence: 87%
“…Intranucleolar chromatin appears frequently at the interface between FCs and DFCs and the perinucleolar chromatin extends forming a bright DAPI-positive ring around nucleoli, containing mainly condensed chromatin partly including NORs and some stretches of decondensed chromatin. Right: treatment with high doses of AMD resolves FC/DFC architecture causing spatial segregation of the three nucleolar components; rDNA retracts into NORs as does most of pol I while the majority of fibrillarin redistributes into the nucleoplasm; NORs and perinucleolar chromatin appear in patches forming nucleolar caps (scheme compiled with data from 10 , 59 , 60 ). …”
Section: Discussionmentioning
confidence: 99%
“…Intranucleolar chromatin appears frequently at the interface between FCs and DFCs and the perinucleolar chromatin extends forming a bright DAPI-positive ring around nucleoli, containing mainly condensed chromatin partly including NORs and some stretches of decondensed chromatin. Right: treatment with high doses of AMD resolves FC/DFC architecture causing spatial segregation of the three nucleolar components; rDNA retracts into NORs as does most of pol I while the majority of fibrillarin redistributes into the nucleoplasm; NORs and perinucleolar chromatin appear in patches forming nucleolar caps (scheme compiled with data from 10,59,60 www.nature.com/scientificreports/ Summing up, we showed that CX-5461 treatment in cultured cells has a profound impact on nucleolar morphology and function of cultured cells. Nucleoli diminish in size and acquire a compact shape surrounded by an increased shell of perinucleolar heterochromatin enriched in repressive chromatin markers.…”
Section: Discussionmentioning
confidence: 99%